Interpretation of Image- Guided Biopsy Results and Assessment - Su Min Ha; Jung Min Chang (Journal of the Korean Society of Radiology, 2023)
The success of image-guided breast biopsy depends on the biopsy method, needle selection, and appropriate technique based on the accurate judgment by the radiologist at biopsy. However, insufficient or inappropriate sampling of specimens may result in false-negative results or pathologic underestimation. Therefore, image–pathology concordance assessments after biopsy are essential for appropriate patient management. Particularly, the assessment of image–pathology concordance can avoid false-negative reports of breast cancer as a benign pathology. Therefore, this study aimed to discuss factors that impact the accurate interpretation of image-guided breast biopsy along with the appropriate assessments.